2007
DOI: 10.1375/acri.40.2.199
|View full text |Cite
|
Sign up to set email alerts
|

The Magistrates Early Referral Into Treatment (MERIT) Pilot Program: Court Outcomes and Recidivism

Abstract: Diversion programs for drug offenders have proliferated in the last decade in the belief that treatment of underlying drug use will decrease an individual's criminal activity. The NSW Magistrates Early Referral Into Treatment (MERIT) program diverts adult offenders with significant drug problems, on bail, from the court to a 3-month intensive drug treatment program. This article reports on the criminal justice outcomes of the Lismore MERIT Pilot Program. Findings indicate that participants who completed the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 16 publications
1
22
1
1
Order By: Relevance
“…In contrast to Passey et al [15], we have identified principal drug as an important predictor of recidivism. Controlling for all other factors in the model, participants with cannabis as their principal drug had a lower risk of recidivism than participants with heroin or methamphetamine as their principal drug.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to Passey et al [15], we have identified principal drug as an important predictor of recidivism. Controlling for all other factors in the model, participants with cannabis as their principal drug had a lower risk of recidivism than participants with heroin or methamphetamine as their principal drug.…”
Section: Discussioncontrasting
confidence: 99%
“…This study replicates the previous finding that completion of MERIT is associated with a reduction in recidivism [12,15]. Compared to program non-completers, Adjusted for all other factors in the model.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The results of the current study confirm the efficacy of the introduction in NSW Magistrates Courts and elsewhere of innovative court‐based diversion programmes (Hunter & McRostie 2001), through which individuals with ID and/or mental health problems and other disorders (such as substance abuse) may be diverted from the CJS into other options including community services, hospitals and rehabilitation. One such example is the Magistrates Early Referral Into Treatment programme (Passey et al. 2007).…”
Section: Discussionmentioning
confidence: 99%